Labour market and fiscal policy - Matthieu Charpe; Slim Bridji (Graduate Institute of International and Development Studies, 2012)
This paper discusses fiscal policy using a DSGE model with search and matching in the labour market. Fiscal policy is effective mainly via its impact through the labour market. Although public intervention tends to crowd out private consumption, public spending also improves the matching between unemployed workers and job vacancies. The mechanism modelled in this paper shares similarity with Baxter & King (1993) and Leeper et al. (2010). The model produces positive fiscal multipliers on impact and in the short term and consistently reproduces the reaction to a spending shock of the main labour market variables such as wages, employment or labour market tightness. These results are similar with that of Monacelli et al. (2010) except that the transmission channel does not depend on the downward adjustment of the reservation wage of workers. The size of the fiscal multiplier increases with the elasticity of matching to spending and is also negatively related with the steady state spending to GDP ratio in the presence of diminishing marginal returns on spending. For large value of the multiplier, there is a crowding in of consumption and investment. Lastly, this model produces output multipliers larger than 1 in the presence of nominal price rigidities.
Keywords: E24; E32; E62; 330; fiscal policy; search; matching; Finanzpolitik; Multiplikator; Beschäftigungseffekt; Preisrigidität; Dynamisches Gleichgewicht; Theorie